A Tale of Two Health-Care Systems: Cost-Utility Analysis of Open Carpal Tunnel Release in Canada and the United States. Issue 1 (February 2017) - Cheung, Kevin; Kaur, Manraj N.; Tolliver, Tyson; Longo, Christopher J.; Naam, Nash H.; Thoma, Achilles
Purpose: Canadian health care is often criticized for extended wait times, whereas the United States suffers from increased costs. The purpose of this pilot study was to determine the cost-utility of open carpal tunnel release in Canada versus the United States. Methods: A prospective cohort study evaluated patients undergoing open carpal tunnel release at an institution in Canada and the United States. All costs from a societal perspective were captured. Utility was measured using validated health-related quality of life (HRQOL) scales—the EuroQol-5D and the Michigan Hand Outcome Questionnaire. Results: Twenty-one patients at the Canadian site and 8 patients at the US site participated. Mean total costs were US $1581 ± $1965 and $2179 (range: $1421-$2741) at the Canadian and US sites, respectively. Health-related quality of life demonstrated significant improvements following surgery ( P < .05). Patient utilities preoperatively and at 6 weeks and 3 months postoperatively were 0.72 ± 0.20, 0.86 ± 0.11, and 0.83 ± 0.16 at the Canadian site and 0.81 ± 0.09, 0.86 ± 0.10, and 0.86 ± 0.12 at the US site. Improvements in HRQOL directly related to surgery were not significantly different between patients in Canada and the United States. American patients, however, attained improved HRQOL sooner due to shorter wait times (27 ± 10 vs 214 ± 119 days; P < .001). The incremental cost-utility of the US system was $7758/quality-adjusted life year gained compared to the Canadian system. Sensitivity analyses confirmed that these results were robust. Conclusion: This pilot study suggests that carpal tunnel surgery is more cost-effective in the United States due to prolonged wait times in Canada.